2016
DOI: 10.1021/acs.jpcc.6b07048
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Prediction of the Electronic Structure and Carrier Mobility in Hexagonal Boron Phosphide Sheet and Nanoribbons

Abstract: Using density functional theory coupled to the Boltzmann transport equation with relaxation time approximation, we study the electronic structure and carrier mobility of graphene-like hexagonal boron phosphide (h-BP) monolayer and H-terminated armchair boron phosphide nanoribbons (ABPNRs). Our results show that the carrier mobility can reach over 10 4 cm 2 V −1 s −1 for electron and 5 × 10 3 cm 2 V −1 s −1 for hole in monolayer sheet. The carrier mobility in the ABPNRs is in the range of 10 3 to 10 4 cm 2 V −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 48 publications
7
55
0
Order By: Relevance
“…As presented in Fig. 5 a, the carrier mobility of BP is 1.50 × 10 4 cm 2 /V/s for electron and 2.74 × 10 3 cm 2 /V/s for hole at 300 K. These result are in accord with previous studies reported by Xie et al (1.37–6.88 × 10 4 cm 2 /V/s) 30 , Zeng et al (0.45–1.36 × 10 4 cm 2 /V/s) 42 and Mohanta et al (0.62–5.77 × 10 4 cm 2 /V/s) 33 . The ultra-high carrier mobility of BP is comparable to other high-mobility materials such as graphene (~ 10 5 cm 2 /V/s) 43 and black phosphorene (~ 10 5 cm 2 /V/s) 44 46 .…”
Section: Resultssupporting
confidence: 92%
“…As presented in Fig. 5 a, the carrier mobility of BP is 1.50 × 10 4 cm 2 /V/s for electron and 2.74 × 10 3 cm 2 /V/s for hole at 300 K. These result are in accord with previous studies reported by Xie et al (1.37–6.88 × 10 4 cm 2 /V/s) 30 , Zeng et al (0.45–1.36 × 10 4 cm 2 /V/s) 42 and Mohanta et al (0.62–5.77 × 10 4 cm 2 /V/s) 33 . The ultra-high carrier mobility of BP is comparable to other high-mobility materials such as graphene (~ 10 5 cm 2 /V/s) 43 and black phosphorene (~ 10 5 cm 2 /V/s) 44 46 .…”
Section: Resultssupporting
confidence: 92%
“…The calculated lattice constants a and b are 3.22 and 5.57 Å, which are very close to those of h-BP monolayer. [42][43][44][45] The bond lengths of B-B, P-P and B-P (see Table 1) are comparable to those of 5 h-BP monolayer (B-P: 1.86 Å), 45 borophene (B-B: 1.62 Å), 46 and phosphorene (P-P: 2.22 Å), 47,48 indicating that the chemical bonds in the borophosphene are strong. Cohesive energy is one of the key factors to evaluate the feasibility of experimental synthesis for the predicted 2D materials, [49][50][51] which is calculated according to the formula of In order to evaluate the stability of borophosphene, phonon spectrum with density of state (DOS) is calculated and shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 81%
“…It should be noticed that the method we used is computationally efficient but physically simple. More sophisticated methods based on Boltzmann transport method with relaxation time approximation can be refered to some recent works [80][81][82][83][84][85] . Table 2 lists the calculated m * , E d , and…”
Section: Bonding Structure and Carrier Mobilitymentioning
confidence: 99%